Palliative care for nursing home patients with dementia: service evaluation and risk factors of mortality - Chu, Chih-Pang; Huang, Cho-Yin; Kuo, Chian-Jue; Chen, Ying-Yeh; Chen, Chun-Tse; Yang, Tien-Wei; Liu, Hsing-Cheng (BMC palliative care, 2020)
Difficulties in prognostication are common deterrents to palliative care among dementia patients. This study aimed to evaluate the effectiveness of palliative care in reducing the extent of utilization of medical services and the potential risk factors of mortality among dementia patients receiving palliative care. We surveyed dementia patients involved in a palliative care program at a long-term care facility in Taipei, Taiwan. We enrolled 57 patients with advanced dementia (clinical dementia rating ≥ 5 or functional assessment staging test stage 7b). We then compared the extent of their utilization of medical services before and after the provision of palliative care. Based on multivariable logistic regression, we identified potential risk factors before and after the provision of palliative care associated with 6-month mortality. The utilization of medical services was significantly lower among dementia patients after the provision of palliative care than before, including visits to medical departments (p < 0.001), medications prescribed (p < 0.001), frequency of hospitalization (p < 0.001), and visits to the emergency room (p < 0.001). Moreover, patients dying within 6 months after the palliative care program had a slightly but not significantly higher number of admissions before receiving hospice care (p = 0.058) on univariate analysis. However, no significant differences were observed in multivariate analysis. The provision of palliative care to dementia patients reduces the extent of utilization of medical services. However, further studies with larger patient cohorts are required to stratify the potential risk factors of mortality in this patient group.